2016
DOI: 10.1080/02670836.2016.1183073
|View full text |Cite
|
Sign up to set email alerts
|

A review on nut coke utilisation in the ironmaking blast furnaces

Abstract: In the ironmaking blast furnaces, nut coke (10-40 mm; 2-23 wt-%) is charged together with the ferrous burden. A systematic review is performed to understand the effects of nut coke use on the permeability, thermal reserve zone (TRZ), reduction kinetics and softening & melting behaviour. State of the art techniques for enhancing reactivity and to lower TRZ temperature are discussed. To utilise nut coke effectively, need of correlational research is expressed on its behaviour with different burden chemistry, car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Despite being beneficial in the iron making process, nut coke is utilised in limited quantity (less than 23 wt%). 5) It was also reported elsewhere that nut coke addition may bring a negative impact on the overall gas permeability due to the regular coke layer thinning. 1,14) Therefore, considering the idea of nut coke use as the replacement of regular coke, it is of utmost importance to understand its impact on the gas permeability, when regular coke layer is thinned due to the higher replacement ratios (more than 20 wt% of the regular coke).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Despite being beneficial in the iron making process, nut coke is utilised in limited quantity (less than 23 wt%). 5) It was also reported elsewhere that nut coke addition may bring a negative impact on the overall gas permeability due to the regular coke layer thinning. 1,14) Therefore, considering the idea of nut coke use as the replacement of regular coke, it is of utmost importance to understand its impact on the gas permeability, when regular coke layer is thinned due to the higher replacement ratios (more than 20 wt% of the regular coke).…”
Section: Introductionmentioning
confidence: 75%
“…[2][3][4] Furthermore, nut coke addition to the ferrous raw material has beneficial effects on enhancing the shaft permeability, lowering thermal reserve zone temperature and improving burden softening-melting properties. 5) Some studies were already performed to understand the influence of nut coke addition on the ferrous burden. For example, Babich et al 6) reported the improvement in the shaft permeability, and therefore the furnace productivity was enhanced (1.5% to 2.5%) with the nut coke mixing (10-20 wt%).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4b shows that the CCB carbon starts gasification at approximately 923 K. Above the CZ, its overall conversion is 85%, indicating that 15% of the CCB carbon would enter the BF lower part. In the present investigation, the influence of the ungasified CCB carbon in the BF lower part was not considered as its behavior has not been distinctly disclosed so far [37]. Figure 5 shows the behavior of a single CCB along a solid flowing path in the BF.…”
Section: Ccb Behavior In Bfmentioning
confidence: 98%
“…An over amount of ungasified carbon particles in BCB may cause clogging, leading to an abnormal BF operation. 41) From Figs. 12(d)-12(e), it is estimated that the average residual carbon content is 0.0 wt.% in case A, 2.2 wt.% in case B, and 3.9 wt.% in case C. Furthermore, the BCB charged near the BF wall would have a carbon content higher than the average value (Fig.…”
Section: Optimzing Bcb Charging Operationmentioning
confidence: 99%